PUBLIC COMMUNICATION STRATEGIES IN SOCIALIZING THE IMPLEMENTATION OF AUTOGATE TECHNOLOGY AT IMMIGRATION CHECKPOINTS - Fassya, Firly Nathania; Fadil Briandito (Multidisiplin Pengabdian Kepada Masyarakat, 2025)
The era of digital transformation has changed the paradigm of public service, particularly in the immigration sector, thru the implementation of autogate technology. This research aims to analyze the public communication strategies implemented in the socialization of autogate technology at Indonesian immigration checkpoints. The research method uses a literature study with a descriptive qualitative approach, analyzing official publications from the Directorate General of Immigration, scientific journals, and documentation of autogate implementation. The research results show that the implementation of autogates has reached nearly 200 units with significant technical efficiency, reducing inspection time from 2-4 minutes to 15-25 seconds per user. The Immigration Information and Communication Technology Section (TIKKIM) implements a multi-platform communication strategy including both conventional and digital media. However, there is a paradox between technical effectiveness and the still low rate of user adoption. The main obstacles identified were less-than-optimal socialization, a passive communication approach, and a lack of comprehensive education for the public. The research recommends restructuring communication strategies to be more engaging and user-oriented, implementing systematic feedback mechanisms, adopting a segmented communication approach, and strengthening inter-institutional collaborative frameworks to create a good communication ecosystem in support of the digital transformation of the immigration sector.